Tathwīr Wasīlat al-Ta'līm 'Alá Asās Pop-Up Book Bimawḍū‘ "Madrasatī al-Jamīlah" fī Ta‘līm al-Lughah al-‘Arabīyah li-Ṭālibāt al-Ṣaff al-‘Āshir bi-al-Madrasah al-‘Āliyah al-Ḥukūmīyah al-Sab’ah Luwu al-Sharqīyah - Rahmawati; Kartini (Al Ibrah: Journal of Arabic Language Education, 2024)
The use of educational tools plays a crucial role in the learning process and must be appropriately selected and adapted to students' needs. One such tool is the pop-up book, which can enhance students' interest in learning Arabic by providing unique and engaging visuals. This research aims to: 1) understand the development process of an educational tool based on pop-up books to support Arabic language teaching for tenth-grade students at SMA Negeri 7 Luwu Timur, and 2) determine the effectiveness of this pop-up book-based educational tool. Utilizing an R&D research type with a 4D model, the study found that expert validation scores were 98.18% for content (very valid), 96.92% for media (very valid), and 94% for educational aspects (very valid). Small group trials scored 91.2% (highly satisfactory), and large group trials scored 90.12% (highly satisfactory). Thus, the pop-up book is deemed highly effective for teaching Arabic to tenth-grade students. ملخص استخدام الأدوات التعليمية يلعب دورًا حاسمًا في عملية التعلم ويجب اختيارها وتعديلها بشكل مناسب لتلبية احتياجات الطلاب. إحدى هذه الأدوات هي كتاب البوب أب، الذي يمكن أن يعزز اهتمام الطلاب بتعلم اللغة العربية من خلال توفير صور فريدة وجذابة. يهدف هذا البحث إلى: 1) فهم عملية تطوير أداة تعليمية قائمة على كتب البوب أب لدعم تدريس اللغة العربية لطلاب الصف العاشر في المدرسة الثانوية الحكومية 7 لووو الشرقية، و 2) تحديد فعالية هذه الأداة التعليمية القائمة على كتب البوب أب. باستخدام نوع البحث R&D مع نموذج 4D، وجدت الدراسة أن درجات التحقق من الخبراء كانت 98.18% للمحتوى (صحيح جدًا)، 96.92% للوسائط (صحيح جدًا)، و94% للجوانب التعليمية (صحيح جدًا). تجارب المجموعة الصغيرة حصلت على 91.2% (ممتاز جدًا)، وتجارب المجموعة الكبيرة حصلت على 90.12% (ممتاز جدًا). وبالتالي، يعتبر كتاب البوب أب فعالًا للغاية لتدريس اللغة العربية لطلاب الصف العاشر